Bariatric Surgery Closure During COVID-19 Lockdown in Italy: The Perspective of Waiting List Candidates - Emanuela Bianciardi; Claudio Imperatori; Cinzia Niolu; Michela Campanelli; Marzia Franceschilli; Lorenzo Petagna; Francesca Zerbin; Alberto Siracusano; Paolo Gentileschi (Frontiers Media S.A., 2020)
Background: From the beginning of March 2020, lockdown regimens prevented patients with obesity from receiving bariatric surgery. Surgical emergencies and oncological procedures were the only operations allowed in public hospitals. Consequently, patients with morbid obesity were put in a standby situation. With the aim at exploring the viewpoint of our future bariatric surgery patients, we built a questionnaire concerning obesity and COVID-19.Method: A total of 116 bariatric surgery candidates were approached using a telephonic interview during the Italian lockdown.Results: Of the total sample, 73.8% were favorable to regular bariatric surgery execution. Forty percent were concerned about their own health status due to the COVID-19 emergency, and 61.1% were troubled by the temporary closure of the bariatric unit. The majority of the sample were eating more. Forty-five percent and the 27.5% of patients reported a worsening of the emotional state and physical health, respectively. Most of the patients (52.2%) considered themselves more vulnerable to COVID-19, especially individuals with class III obesity. Patients who reported an increased consumption of food were younger (43.44 ± 12.16 vs. 49.18 ± 12.66; F = 4.28, p = 0.042). No gender difference emerged.Conclusion: The lockdown had a negative result on Italian patients' psychological well-being and eating habits. The majority of patients would have proceeded with the surgery even during the COVID-19 emergency. Effective management and bariatric surgery should be restarted as soon as possible.